2019
DOI: 10.1371/journal.pone.0226305
|View full text |Cite
|
Sign up to set email alerts
|

A world map of evidence-based medicine: Density equalizing mapping of the Cochrane database of systematic reviews

Abstract: Systematic reviews represent the core and backbone of evidence-based medicine (EBM) strategies in all fields of medicine. In order to depict a first global sketch of the international efforts in the Cochrane database systematic reviews (CDSR), we analyzed the systematic reviews of the Cochrane database. Our global maps of systematic reviewing offer intriguing structural insights into the world of EBM strategies. They demonstrate that for the CDSR, the UK and Commonwealth countries take the lead position. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…In Mexico, 20% of accredited curriculums offer single EBM courses as required, accounting for 0.08% of the total academic credits. These findings align with the limitations observed at the global level 38. Students also learn during informal interactions with their teachers and through organisational culture; however, academic instructional offerings ensure that the educational objectives of the medical school are met 39.…”
Section: Discussionsupporting
confidence: 78%
“…In Mexico, 20% of accredited curriculums offer single EBM courses as required, accounting for 0.08% of the total academic credits. These findings align with the limitations observed at the global level 38. Students also learn during informal interactions with their teachers and through organisational culture; however, academic instructional offerings ensure that the educational objectives of the medical school are met 39.…”
Section: Discussionsupporting
confidence: 78%
“…It is worth highlighting that the reporting of SRs of RCTs and RCTs in The New York Times and The Times , respectively, may be seen as an indicator of good quality journalism. It should also be noted that the USA and the UK are the countries that produce the most Cochrane SRs [ 50 ] and that newspapers tend to report more on domestically produced science [ 23 ]. On the other hand, the over-representation of animal/laboratory studies in the business newspapers, which is mainly down to The Wall Street Journal , is expected as preclinical microbiome research (representing 30.4% of microbiome studies in PubMed) is the first step towards developing microbiome therapies, and that is where most companies’ initial efforts begin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, countries that belong to the Commonwealth have been separated (cf. Encyclopaedia Britannica, 2021), due to their stronger commitment to evidence-based medicine (Groneberg et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While marking seventh with 4.8%, its portions grew steadily year over year, taking the second rank in 2015 with over 1000 items and 18% of overall share. Groneberg et al have shown that strong commitments towards evidence-based medicine can be associated with the Commonwealth (Groneberg et al, 2019). Similarly, the analysis of document types shows that such countries, especially the U.K., Canada, Australia or New Zealand, produce higher rates of systematic reviews and its PRISMA-based counterpart than other leading science nations (Figs.…”
Section: Systematic Reviews By Countriesmentioning
confidence: 95%